2019
DOI: 10.1080/09712119.2019.1580584
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide structure of prion protein gene in Egyptian camels

Abstract: The prion protein is coded by the PRP gene which is active in the brain and several other tissues. The functions of normal PrPs are related to energy production, protein degradation and DNA replication. Prions are the essential factor for the transmissible spongiform encephalopathies (TSEs) in different mammalian species. The present study aimed to identify the nucleotide characterization of the PRP gene in six camel breeds reared in Egypt. Genomic DNA which was extracted from 80 camels belonging to six breeds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…All 50 individuals representing eight breeds of Ethiopian C. dromedarius were monomorphic for the PRNP gene and were 100% identical to the nucleotide sequences reported for the CPD–positive individuals in Algeria ( Babelhadj et al, 2018 ). Most studies ( Abdel-Aziem et al, 2019 ; Adeola et al, 2024 ; Babelhadj et al, 2018 ; Kaluz, Kaluzova & Flint, 1997 ; Tahmoorespur & Jelokhani Niaraki, 2014 ; Tahmoorespur & Jelokhani Niaraki, 2014 ; Xu et al, 2012 ; Zoubeyda et al, 2020 ) report low variability in the PRNP gene among Camelus (0.42% reported herein). Three synonymous nucleotide substitutions (T231C, T243A, and T264C), identified as phylogenetically informative by Parsimony analyses, differentiated the two Camelus species.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…All 50 individuals representing eight breeds of Ethiopian C. dromedarius were monomorphic for the PRNP gene and were 100% identical to the nucleotide sequences reported for the CPD–positive individuals in Algeria ( Babelhadj et al, 2018 ). Most studies ( Abdel-Aziem et al, 2019 ; Adeola et al, 2024 ; Babelhadj et al, 2018 ; Kaluz, Kaluzova & Flint, 1997 ; Tahmoorespur & Jelokhani Niaraki, 2014 ; Tahmoorespur & Jelokhani Niaraki, 2014 ; Xu et al, 2012 ; Zoubeyda et al, 2020 ) report low variability in the PRNP gene among Camelus (0.42% reported herein). Three synonymous nucleotide substitutions (T231C, T243A, and T264C), identified as phylogenetically informative by Parsimony analyses, differentiated the two Camelus species.…”
Section: Discussionmentioning
confidence: 62%
“…Previous genetic studies of dromedary camels in Algeria, Egypt, and Ethiopia ( Cherifi et al, 2017 ; Legesse et al, 2018 ) reported a lack of morphological, genetic variation, and population structure indicating homogeneity in the nuclear genome of C. dromedarius . In addition, low variability of camel PRNP sequences has been reported compared to other sequences representative of dromedary camels ( Abdel-Aziem et al, 2019 ; Babelhadj et al, 2018 ; Kaluz, Kaluzova & Flint, 1997 ; Tahmoorespur & Jelokhani Niaraki, 2014 ; Xu et al, 2012 ; Zoubeyda et al, 2020 ). Given the broad distribution of camel breeds across northern Africa and the apparent lack of genetic variation among breeds, it is hypothesized that Ethiopian dromedary camels will have similar PRNP genotypes to other dromedary camels.…”
Section: Introductionmentioning
confidence: 97%
“…Contrarily, previous studies on polymorphism of PRNP gene in Nigerian small ruminants, 29 SNPs (14 non-synonymous and 23 novel SNPs) and 19 SNPs (14 non-synonymous SNPs with T718C as a novel SNP) were revealed in Nigerian goats and sheep, respectively [ 30 , 34 ]. Recent studies have reported low variation in dromedary PRNP gene in Egypt and Iran [ 53 , 54 ]. Two non-synonymous SNPs (G205A and G401A) were identified in PRNP gene in Algerian dromedary [ 55 ] but not detected in the present study for Nigerian camel.…”
Section: Discussionmentioning
confidence: 99%